STRUKTUR POPULASI KUMBANG TANDUK (Orycetes rhinoceros) DI AREA PERKEBUNAN KELAPA SAWIT MASYARAKAT DESA KENANTAN KABUPATEN KAMPAR-RIAU - Yustina '; Yuslim Fauziah; Rika Sofia (Biogenesis, 2012)
The study has been conducted to determine the structure of horn beetle populations (Orycetes rhinoceros) In Palm Oil Plantation Village Community Kenantan - Riau Kampar regency, held in June-September 2011. Determination of purposive sampling stations were done by considering the age of oil palm trees found in the study site. Samples taken Orycetes rhinoceros with three ways, namely, using mist nets, ferotrap, and direct sampling. Parameters measured include: biological parameters of abundance, age structure, and biomass. While the physical-chemical parameters of temperature, humidity, and wind speed. The results showed that the population abundance at the station I found the pupa 43 tail, tail imago1 73, and 60 head while imago2 abundance at station II, the pupa 30 tails, 61 imago1 imago2 tails and 40 tails, the highest abundance occurred in August and abundance lowest occurred in June, the age structure is most commonly found in the age structure of the imago1 stadia breeding period and the highest biomass of biomass on imago1 stadia.Keywords: Coleoptera, Orycetes rhinoceros.